2011
DOI: 10.1007/s10669-011-9335-8
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of oil spills in temperate and tropical coastal marine environments

Abstract: Oil is the world's primary source of non-renewable energy, and it has also contaminated ocean coastlines due to spills. It is therefore important to have remediation treatments that are both effective, and ecologically not harmful. Current in situ bioremediation methods consist primarily of biostimulation, through addition of nutrients, and bioaugmentation, the addition of hydrocarbon degrading microorganisms. The purpose of this article is to discuss successful and unsuccessful remediation through the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…also shows maximum enzyme activity at temperature 37°C and pH 7. The microbial treatments are capable of oil remediation in temperate and tropical regions (Mercer and Trevors, 2011). The temperature specific enzymatic activity of lipase is maximum at relatively high 37°C ensures the activity of this enzyme as a bioremediate to restore oil contaminated sites of equatorial and temperate regions.…”
Section: Discussionmentioning
confidence: 99%
“…also shows maximum enzyme activity at temperature 37°C and pH 7. The microbial treatments are capable of oil remediation in temperate and tropical regions (Mercer and Trevors, 2011). The temperature specific enzymatic activity of lipase is maximum at relatively high 37°C ensures the activity of this enzyme as a bioremediate to restore oil contaminated sites of equatorial and temperate regions.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of methods to control oil spills in marine shorelines and freshwater ecosystems have been established but still the problem exists. These methods were closely researched and outlined in several technical documents [ 25 , 30 , 33 , 43 , 51 , 52 , 53 , 54 ]. Floating booms and barriers, oil collection materials, oil collection vessels, absorbing materials, chemical dispersants, surfactants, physical degradation, biodegradation and on-site oil combustion are the most common methods and techniques for oil containment and removal at sea [ 30 ].…”
Section: Petroleum Hydrocarbon Treatmentsmentioning
confidence: 99%
“…Bioaugmentation strategies are based on the addition of efficient degrading microbial strains in order to boost PAH biodegradation (Hou et al 2005;Tyagi et al 2011). Different studies have demonstrated the potential of specific microbial strains for PAH degradation in environmental matrices including sediments (Mapelli et al 2017;Mercer and Trevors 2011;Perelo 2010). Usually, under the patents describing bioaugmentation approaches, bacteria strains were the most commonly used among microbes for the formulation of bioremediation products as illustrated in Fig.…”
Section: Bioaugmentation Strategiesmentioning
confidence: 99%